Teaching mindfulness in prison settings: a grounded theory of strategies to promote engagement and empowerment. Issue 1 (2nd January 2022) - Hilert, Alexander J.; Haskins, Natoya
Abstract: Mindfulness-based interventions have been increasingly recognized as a way to promote the mental health and well-being of individuals experiencing incarceration. However, little is known about the ways in which experienced mindfulness teachers who volunteer in correctional settings facilitate programming. Using a constructivist grounded theory approach, this study explored the teaching practices of volunteers who currently facilitate mindfulness programs in correctional settings. A total of fifteen volunteer meditation teachers along with three former group members were interviewed. The researcher utilized interview data to construct a grounded theory which conceptualizes the systemic barriers volunteers and participants face, empowering facilitation strategies, and facilitator and group characters which impact the learning outcomes of participants. The results of this grounded theory illustrate culturally responsive mindfulness facilitation strategies counselors can use with individuals who are incarcerated. Suggestions for future research and implications are presented.